The Mediating Effect of Perceived Organizational Support on the Relationship between Authentic Leadership and Turnover Intention - Ladao, Lorreine (Animo Repository, 2022)
The paper aims to examine the effects of authentic leadership and perceived organizational support on employees’ turnover intention and investigate the mediating effect of perceived organizational support on the relationship between authentic leadership and turnover intention. The participants of the study were the 203 employees from select business process outsourcing companies within Pampanga, Philippines. The study implemented a predictive-causal research approach and a quantitative research design to gauge the relationship between perceived organizational support, authentic leadership, and turnover intention. Partial least squares–structural equation modeling was further employed to measure the direct and indirect effects of the structural model. The findings revealed that authentic leadership and perceived organizational support are significantly and negatively related to turnover intention. Moreover, a significant and positive relationship between authentic leadership and perceived organizational support was observed. Perceived organizational support was also found to significantly mediate the negative relationship between authentic leadership and turnover intention. The present study offers a new perspective on perceived organizational support as a mediator on turnover intentions in the Philippine setting. It also provides a view on authentic leadership as an important leadership quality in reducing employee withdrawal behaviors.